Eco-Geography of Coastal Areas: Sosio-Economy Dynamic of Land Ownership of Coastal Areas of Indonesia - Baiquni, M (Forum Geografi, 1997)
Indonesia constitute an archipelagic state which passesses resource of ocean, ecosystem of coast area and social economy dynamics of various maritime society. The nation of Indonesia had ever been welknown as a maritime nation which dominated Nusantara territorial waters as far as neighbour state. Fish cultivation in embankruentÂ system has been being known since the era of Mojopahit Kingdom and likewise boat industry was held along the north-oast of Java which was ever glorius in the beginning of Dutch Colonialism. But, up to now why a large part of Indonesian fishermen are still using simple technology and method in fishery and fish cultivation? Change in policy within Dutch era development. Which was farm land oriented and plantation had influenced the maritime tradition slip off. Opening of railway and land tract transportation in Java had changed economic ativity pattern of the oast area to hinterland. Investment and human resource were councentrated to farmland development and plantation was directed to export so that it affected the coast area slip off which was basically fishery activity. Development after independence, mainly in the era of New Order, it started from farming activity raised to industry society. Coastal area came back to develop with industrial growth in the urbans of Java north coast. Nevertheless development in fishery does not yet return to show the sign of glorious untill the end of this age. It isÂ hoped that, with properly judment of the islands coastal area out of Java, goverment will directÂ its policy and investment to develop the new maritime society to go against the glorious in the 21st century.